2021
DOI: 10.3892/etm.2021.10687
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‑based complementary and alternative medicine bioinformatics approach through network pharmacology and molecular docking to determine the molecular mechanisms of Erjing pill in Alzheimer's disease

Abstract: Erjing pill, a Traditional Chinese Medicine (TCM) formulation composed of Polygonatum sibiricum and Lycium chinense, has an important role in the treatment of Alzheimer's disease (AD). However, the underlying mechanisms of the action of Erjing pill in AD have remained elusive. In the present study, the key ingredients of Erjing pill were investigated and the active components and their mechanisms of action on AD were analyzed based on networks pharmacology. By using the TCM and TCM Systems Pharmacology and dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Current drugs applied to AD with a single target can only delay the symptoms of AD to a certain extent and have more serious side effects. [ 32 ] Studies have shown that TNF‐α, IL‐6, and IL‐1β levels are significantly elevated in the serum and brain of AD patients and AD animal models. Increased pro‐inflammatory levels promote Aβ production and tau protein phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Current drugs applied to AD with a single target can only delay the symptoms of AD to a certain extent and have more serious side effects. [ 32 ] Studies have shown that TNF‐α, IL‐6, and IL‐1β levels are significantly elevated in the serum and brain of AD patients and AD animal models. Increased pro‐inflammatory levels promote Aβ production and tau protein phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In some recent clinical studies, it has been claimed that there is no relationship between Ca level and 25-OH D3 level after total thyroidectomy. Singh et al [22] reported that preoperative 25-OH D3-vitamin level did not affect postoperative Ca level in patients who underwent total thyroidectomy. In the study conducted by Al-Khatib et al [23], it was reported that low 25-OH D3 level affects the early postoperative Ca level but not the longterm Ca level in patients who underwent total thyroidectomy.…”
Section: -Oh D3 Plays An Important Role In Ca Metabolism By Increasing the Absorption Ofmentioning
confidence: 99%
“…Only compounds that complied with three or more of the aforementioned characteristics were maintained in the database. L. sativum constituents' oral bioavailability (OB) was also estimated (Yang et al, 2021). It shows how much of a drug dosage taken orally reaches the therapeutic site of action without change.…”
Section: Adme Filtration Of L Sativum Constituentsmentioning
confidence: 99%